The Perception of Auditors in the Measurement of Instruments Financial Institutions at Fair Value in Financial Institutions - Paulo Cesar de Melo Mendes; Jorge Katsumi Niyama; Cesar Augusto Tiburcio Silva (BBR: Brazilian Business Review)
The objective of the research is to analyze the auditors' perception regarding the measurement of the fair value of complex financial instruments level 3 in financial institutions. A questionnaire was applied with a sample of 62 independent auditors with technical qualification in financial institutions of large audit firms among partners, managers and senior auditors. The tools used were the Logistic Regression Test (LOGIT); The KruskalWallis test, and the matching analysis test. Subjectivity was an implicit characteristic in the process where the auditors remained conservative. However, differences of values were identified that resulted in immaterial issues and an indication of divergences in the measurement of accounting estimates. As a suggestion of improvement in the audit processes, a more robust academic formation and the inclusion of a financial expert in the teams were identified. Opinions diverge as to the partners and managers, where they pointed out more agreement with the issues than the managers.